Energia metabolizável aparente para poedeiras Isa Label mantidas em ambiente de alta temperatura - Macchi, Paloma de Matos (2015)
Brazil stands out in poultry production as the largest exporter and third largest producer of chicken, and among the ten largest producers of eggs. The demand for food and population growth make the poultry production chain essential to agribusiness, regional economy and strengthening family agriculture, providing highly nutritious affordable food. Genetic improvements and research in pet nutrition favored the success of the poultry industry in the country, however, there is little research on nutritional requirements for slow growth bloodlines in hot climate regions. The Isa Label is a strain with naked neck, slow growth bloodlines with two option for products, which has been widely used by farmers for being good producer of eggs and meat have with appreciable flavor. The amount of metabolizable energy used in feed is conditional factor for productivity of laying in high temperature conditions, and has considerable weight in food costs. The aim of this study was to determine the requirement of apparent metabolizable energy (AME) to Isa Label bird dual purpose in laying phase, 52 weeks old, under high temperature conditions, by evaluating performance, quality eggs and economic viability. They were distributed at random 90 laying in five treatments with nine replicates of two birds each. The treatments were 2,600; 2,675; 2,750; 2,825 and 2,900 kcal / kg of EMA in the feed. We evaluated: feed intake and EMA, laying rate, egg weight, egg mass, feed conversion and energy per mass and dozen eggs; and quality characteristics of eggs. The economic analysis was performed with the number of eggs produced, feed consumption and price per kilogram of feed. The results were productive performance and egg quality were statistically analyzed by polynomial regression with probability <5% significance level. The results of the economic analysis were submitted to descriptive statistics. Increasing the EMA level in poultry feed Isa Label in laying phase, not compromise performance between 52 and 64 weeks of age. The level 2,778 kcal / kg of EMA in the ration showed lower feed intake, while the 2,638 kcal / kg EMA level in the diet had lower power consumption under high temperature environment conditions. Internal and external quality of the eggs was not affected by EMA level in feed, but increased EMA in diets increased the width of the albumen and egg. The use level of 2,675 kcal / kg of EMA is economically viable for poultry Isa Label in stance phase, from 52 to 64 weeks of age under high temperature conditions